2015
DOI: 10.5562/cca2686
|View full text |Cite
|
Sign up to set email alerts
|

Ferryl and Ferrate Species: Mössbauer Spectroscopy Investigation

Abstract: High-valent iron species of oxidation states +4, +5, and +6, have been involved as intermediates in enzymatic reactions, in green organic synthesis, and in purification and disinfection of water. Many of these species have been synthesized to understand their role in different systems, which include ferryl complexes (oxoiron(IV) (Fe IV =O), oxoiron(V) (Fe V =O)), iron(IV / V / VI)-nitride complexes, and ferrates ((Fe VI O4 2-, Fe(VI), Fe V O4 3-, Fe(V), and Fe IV O4 4-, Fe(IV)). Ferryl and iron-nitride complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…It has been found that the biological activities of the discussed compounds are considerably increased when they are bonded into metal complex molecules. For example, such effects have been observed for Co(II), Ni(II), Cu(II) and Zn(II) chelates with several ligands, including 2-thiophenecarboxylic acid tested, on some selected fungi [5]. In addition, the Co(II), Ni(II) and Cu(II) complexes with 2-thiophenecarboxylic acid have received increasing attention as potential anticancer drugs [6].…”
Section: Introductionmentioning
confidence: 96%
“…It has been found that the biological activities of the discussed compounds are considerably increased when they are bonded into metal complex molecules. For example, such effects have been observed for Co(II), Ni(II), Cu(II) and Zn(II) chelates with several ligands, including 2-thiophenecarboxylic acid tested, on some selected fungi [5]. In addition, the Co(II), Ni(II) and Cu(II) complexes with 2-thiophenecarboxylic acid have received increasing attention as potential anticancer drugs [6].…”
Section: Introductionmentioning
confidence: 96%
“…Using Density Function Theory (DFT) calculations, Poleshchuk et al estimated the chemical shift of “Fe VIII O 4 ” to be δ = −1.40 mm s −1 (with respect to α-iron) and that the Fe-O bond was calculated to be 1.586 Å, assuming all Fe-O bonds are identical [ 97 ]. Sharma & Zboril (2015) produced a linear correlation equation between chemical shift and oxidations state of iron [ 98 ], therefore: δ (mm s −1 ) = 1.084 − 0.326 × (oxidation state) …”
Section: Vibrational Spectramentioning
confidence: 99%
“…The instability of FeO 4 2− severely limits its large‐scale application and becomes a bottleneck for further development. [ 38–39 ] On the other hand, such a reaction system is completely against the objective of the green chemical production technology advocated today because a large mass of FeO 4 2− has been consumed to form inorganic waste contaminated by organic tars. [ 40–43 ] Therefore, it is very important to establish a new catalytic system to effectively utilize FeO 4 2− .…”
Section: Introductionmentioning
confidence: 99%